Profit Sharing dalam Pengelolaan Rumah Makan â€œPadangâ€ - Solihin, Fauzi (Bina Nusantara University, 2004)
Article discusses profit sharing in running a â€œPadangâ€ restaurant. Profit sharing always increase sense of belonging every employee andÂ supportÂ theÂ Â managementÂ Â function.Â ItÂ Â canÂ Â beconcluded that profit sharing can motivated employee to increase working performance and increase sense of belonging and responsibility. It also can increase continuous improvement team work between employee.